The Motif of Love in Vikas Sharma's Love's Not Time's Fool (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Love is an emotion born with a living organism in this cosmos. A few philosophers, writers, and psychologists have tried their best to bind this unbounded emotion through some words of definition but failed or succeeded little.  Love is not a negative thing or romantic thing related to husband-wife or lover-beloved rather it has different colors like passionate love, spiritual love, parental love, sibling love, universal love, etc. It is an emotional attachment between the two or more. It is an individual's transaction of heart, will, desires, and faith unconditionally with complete submission of one's will and service to the loved one/ones. In this modern and industrialized world, the concept of love is changing rapidly in different directions resulting in new and modern relationships with a tinge of boldness and open-mindedness. Vikas Sharma, an emerging novelist writing in both Hindi and English, has focused on this changing concept or motif of love in his writings. His love novel Love's Not Time's Fool (2021) presents a glimpse of different shades of love in human life in the 21st century. Richa Pandit alias Richa Vaidik, the protagonist of the novel, is a lady with a feministic ideology and is completely aware of her desires in this mortal world during the pandemic crises. She is broadminded enough to fulfill her desires and to develop physical relationships with more than one male partners in India or abroad.